Wear resistance of abradable-conductive powder deposited by using hvof with different surface preparation and spray distance - Hendy Roesma Wardhana; Rd. Dadan Ramdan; Budi Prawara; Erie Martides; Riza Wirawan; Bambang Widyanto; Rochim Suratman; Irma Pratiwi (University of Muhammadiyah Jakarta, 2022)
Along with many material failures due to worn steel components, HVOF (High Velocity Oxygen Fuel) coating based abradable material can be solution to overcome this problem. However, abradable-conductive material is still rarely used for coating, therefore it needs investigation to find out the optimum parameters of process. In this work, the surface treatment on substrate was carried out by the different methods such blasting, etching, and blasting-etching to obtain the rough surface. The spraying distance of HVOF process was varied on 20 cm and 30 cm. Blasting-etching are able to achieve the roughest surface of substrate. Meanwhile, the spray distance of 20 cm produces thicker layer than the longer spray distance. The combination of blasting-etching and the shorter spray distance are able to reach the optimum wear resistance as presented in pin-on-disc test.